2013
DOI: 10.1080/13573322.2013.858625
|View full text |Cite
|
Sign up to set email alerts
|

Lived experience and community sport coaching: A phenomenological investigation

Abstract: Cronin, Colum and Armour, Kathleen M. (2015) Lived experience and community sport coaching: a phenomenological investigation. Sport, Education and Society, 20 (8). pp. 959-975.Downloaded from: http://insight.cumbria.ac.uk/2006/ Usage of any items from the University of Cumbria's institutional repository 'Insight' must conform to the following fair usage guidelines.Any item and its associated metadata held in the University of Cumbria's institutional repository Insight (unless stated otherwise on the metadata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 42 publications
0
33
0
1
Order By: Relevance
“…Indeed, a phenomenological approach using such an attitude has revealed that participation coaching in community settings includes much more everyday activity (e.g. relationships with others such as teachers and private sector providers) than hitherto acknowledged by researchers (Cronin and Armour, 2013). That study also revealed that community coaching includes a "delivery mode visible in the public arena and a 'hidden' largely unknown, private world used predominantly for planning and organising" (Cronin and Armour, 2013 p1).…”
Section: Why An Interpretive Phenomenological Approach To Youth Perfomentioning
confidence: 97%
See 4 more Smart Citations
“…Indeed, a phenomenological approach using such an attitude has revealed that participation coaching in community settings includes much more everyday activity (e.g. relationships with others such as teachers and private sector providers) than hitherto acknowledged by researchers (Cronin and Armour, 2013). That study also revealed that community coaching includes a "delivery mode visible in the public arena and a 'hidden' largely unknown, private world used predominantly for planning and organising" (Cronin and Armour, 2013 p1).…”
Section: Why An Interpretive Phenomenological Approach To Youth Perfomentioning
confidence: 97%
“…Indeed, for some time now, coaching literature and prescribed practice have been criticised for oversimplification, reductionism, and a failure to recognise the social and cultural influences upon coaching (Cushion, Armour, & Jones, 2006). Legislative literature is therefore mostly divorced from the grounded realities of coaching practice as lived by the coaches themselves, and the context in which they exist (Miller, et al, 2015;Miller & Cronin, 2013;Cronin & Armour, 2013).…”
Section: Why An Interpretive Phenomenological Approach To Youth Perfomentioning
confidence: 99%
See 3 more Smart Citations